The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1515/jpm-2014-0295
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the prenatal programming effects of glucocorticoids: are there alternative treatments for the induction of antenatal lung maturation?

Abstract: The efficacy and safety of these alternative agents are differentiated and none up to now can be recommended as an alternative to GCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 117 publications
(169 reference statements)
0
2
0
1
Order By: Relevance
“…Antenatal steroidler fetal surfaktanın yapısında bulunan fosfolipid ve protein metabolizması üzerine direkt etki göstererek akciğer matürasyonunu hızlandırırlar (6). Ayrıca steroidler fetal tiroid hormonu aktivitesini artırarak fetal akciğer matürasyonunu indirekt olarak da hızlandırabilmektedir (7).…”
Section: Yazarların Katkısı / Contribution Of the Authors: Anik Aunclassified
“…Antenatal steroidler fetal surfaktanın yapısında bulunan fosfolipid ve protein metabolizması üzerine direkt etki göstererek akciğer matürasyonunu hızlandırırlar (6). Ayrıca steroidler fetal tiroid hormonu aktivitesini artırarak fetal akciğer matürasyonunu indirekt olarak da hızlandırabilmektedir (7).…”
Section: Yazarların Katkısı / Contribution Of the Authors: Anik Aunclassified
“…In pregnancies threatened with preterm birth, antenatal steroid (ANS) treatment to induce fetal lung maturation and to reduce neonatal morbidity and mortality is common practice [1] and appropriate alternatives currently do not exist [2]. We have previously shown that ANS treatment in normally grown singleton and twin pregnancies reduced in a dose-dependent and sex-specific manner fetal weight gain, length and head circumference compared with gestational age-matched controls [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reports that maternal serum concentrations of magnesium are lower following MgS04 infusion in mothers with twins compared with singleton gestations which may help account for the lesser neuroprotective effects of this agent in multiple gestations [16]. Finally, Justus and colleagues examine the full gamut of alternatives to corticosteroids for enhancing lung maturity and present these agents' risk benefit data in either animal studies or human clinical trials [17]. Taken together, the current issue of the Journal of Perinatal Medicine contains rich offerings for clinicians and clinical researchers interested in reducing the perinatal morbidity and mortality attendant preterm birth.…”
mentioning
confidence: 99%